Climate Change Litigation and Environmental Justice: The Evolving Role of International Legal Frameworks - Gustika Sandra; Abdul Ghoni; Tomi Apra Santosa; Muhammad Sofwan Jauhari; Riki Rosadi (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
Climate change has become a multidimensional issue that not only impacts the environment but also poses serious challenges to social justice and human rights. In recent decades, climate change litigation has emerged as a strategic legal instrument to hold states and non-state actors accountable for their failure to prevent and mitigate the impacts of climate change. This article aims to analyze the growing role of the international legal framework in supporting climate change litigation and strengthening the principles of environmental justice. This research employs a doctrinal study method with a normative approach to international legal instruments, international and national court decisions, and global policy documents related to climate change. The results of the study indicate that although international law does not yet explicitly regulate binding climate change litigation mechanisms, various international legal principles such as due diligence obligations, state responsibility, the precautionary principle, and intergenerational justice have been progressively utilized in judicial practice. Furthermore, the international legal regime on climate change and human rights increasingly serves as a normative framework that strengthens claims to justice for vulnerable groups who are most affected. This research confirms that climate change litigation serves not only as a means of law enforcement but also as a catalyst for the transformation of public policy and global environmental governance. Therefore, strengthening the integration between international environmental law and the human rights regime is key to achieving sustainable environmental justice.